2021
DOI: 10.3390/nu13093078
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Implementing Healthy School Canteen Intervention among Malaysian Adolescents: A Qualitative Study

Abstract: This study evaluated implementing a school-based intervention to promote healthier dietary habits in the school environment among Malaysian adolescents using qualitative methods. This qualitative study was conducted in four secondary schools in Perak and Selangor (two urban and two rural schools) that received the intervention (either training or training and food subsidy). A total of eight focus groups (68 students aged 15 years old) and 16 in-depth interviews were conducted with canteen operators, school con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…However, we did not observe any significant difference in reduction when a comparison was made between arms (control, intervention one and two). Although positive effects of food subsidization and training on healthy cooking in this study were not observed, the school-based intervention showed promising results in improving the dietary intake among adolescents [19]. Moreover, affordability was associated with better dietary intake [19].…”
Section: Effects Of Interventions On Anthropometry Measuresmentioning
confidence: 56%
See 2 more Smart Citations
“…However, we did not observe any significant difference in reduction when a comparison was made between arms (control, intervention one and two). Although positive effects of food subsidization and training on healthy cooking in this study were not observed, the school-based intervention showed promising results in improving the dietary intake among adolescents [19]. Moreover, affordability was associated with better dietary intake [19].…”
Section: Effects Of Interventions On Anthropometry Measuresmentioning
confidence: 56%
“…Although positive effects of food subsidization and training on healthy cooking in this study were not observed, the school-based intervention showed promising results in improving the dietary intake among adolescents [19]. Moreover, affordability was associated with better dietary intake [19].…”
Section: Effects Of Interventions On Anthropometry Measuresmentioning
confidence: 56%
See 1 more Smart Citation
“…The most common reason was that no barriers and facilitators were found ( n = 82). A final 36 articles were included in this review [ 15 , 27 61 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The nutritional quality of foods and drinks purchased by high school students at school canteens is often perceived as being less healthy than lunch brought from home. However, while the availability of items on canteen menus is often reported, only a few studies internationally have investigated the types of products actually purchased by secondary school students at canteens [13,[17][18][19], and no studies have reported data on the nutrient composition of those products.…”
Section: Introductionmentioning
confidence: 99%